1965
DOI: 10.2136/sssaj1965.03615995002900060031x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Liming and Flooding on Manganese Toxicity in Alfalfa

Abstract: Incubation and greenhouse studies showed that regardless of soil pH, flooding increased the content of exchangeable Mn and the Mn content of alfalfa (Medicago sativa L.) grown in a Kellner loamy sand. In the absence of a source of easily decomposable organic matter, Mn mobilization by flooding was considerably slower at a soil pH of 4.7 than at 7.3. Where alfalfa was grown in the soil or where finely milled oat straw was added, flooding mobilized more Mn in the acid than in the neutral soils. Liming promoted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

1967
1967
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 0 publications
0
22
0
1
Order By: Relevance
“…On acid flooded soils, even rice may suffer from Fe toxicity (DeDatta et al 1990). Graven et al (1965) reported that the Mn concentration increased in alfalfa shoots by soil flooding and that the Mn concentration reached a toxic level. Also Drew (1988) found that water logging often induces an increase of Mn and Fe in shoots of wheat and barley.…”
Section: Discussionmentioning
confidence: 99%
“…On acid flooded soils, even rice may suffer from Fe toxicity (DeDatta et al 1990). Graven et al (1965) reported that the Mn concentration increased in alfalfa shoots by soil flooding and that the Mn concentration reached a toxic level. Also Drew (1988) found that water logging often induces an increase of Mn and Fe in shoots of wheat and barley.…”
Section: Discussionmentioning
confidence: 99%
“…In flooded soils the reduced, divalent forms of iron and manganese occur, which are more soluble and therefore available to plants (Gotoh & Patrick, 1972, 1974. Toxicity of iron (Martin, 1968;Jones & Etherington, 1970;Wheeler, Al-Farraj & Cook, 1985;Etherington & Thomas, 1986) and manganese (Graven, Attoe & Smith, 1965;Jones, 1972;Singer & Havill, 1985;Etherington & Thomas, 1986) may limit growth and distribution of certain species in soils prone to waterlogging.…”
Section: Introductionmentioning
confidence: 99%
“…root growth 3. Manganese may also become toxic to plant growth in acid soils 28, particularly under flooded conditions 20.…”
Section: Introductionmentioning
confidence: 99%